Social Experience-Dependent Myelination: An Implication for Psychiatric Disorders - Michihiro Toritsuka; Manabu Makinodan; Toshifumi Kishimoto (Neural Plasticity)
Myelination is one of the strategies to promote the conduction velocity of axons in order to adjust to evolving environment in vertebrates. It has been shown that myelin formation depends on genetic programing and experience, including multiple factors, intracellular and extracellular molecules, and neuronal activities. Recently, accumulating studies have shown that myelination in the central nervous system changes more dynamically in response to neuronal activities and experience than expected. Among experiences, social experience-dependent myelination draws attention as one of the critical pathobiologies of psychiatric disorders. In this review, we summarize the mechanisms of neuronal activity-dependent and social experience-dependent myelination and discuss the contribution of social experience-dependent myelination to the pathology of psychiatric disorders.